(untitled) (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article is devoted to the analysis of the nature of social roles in relations between grandparents and grandchildren. The author considers the most important roles of the older generation in the family — guardians, counselors and consultants, friends, guardians of family traditions and family history. The purpose of empirical author’s analysis is to compare the values of the functions and roles performed by the older generation in the family and their impact on the life and development of grandchildren